Da Barra do Rio aos parrachos: duas realidades sociorganizacionais no litoral Norteriograndense - Vale, Maria Páscoa do (2013)
Observing that social capital is considered crucial for the consolidation of an association, this paper analyzes how different groups associative absorb the concept of membership and how to manage routing in their actions to the social interest. The research aimed to evaluate two central forms of association, based on the concept of Pierre Bourdieu (1980) on social capital, stressing that its distribution and perception are uneven and depends on the ability of ownership of different social groups. Accordingly, took up two organizations community based one in - Barra do Rio and another in Maracajaú - whose main activity is the exploitation in the coastal tourist norteriograndense. Once processed the data, it became clear that, despite the purpose for the association has been motivated by exploration in both organizations, each differently appropriates its capital. While one maintains a feelings of togetherness, trust and satisfaction of group work, the other one, feelings are stifled by individualism, mistrust among their members that although they see the association as something important for the growth and strengthening of the group, working individually